Efeito do Enalapril e do Captopril sobre a respota imune in vivo - Isoton, Deborah de Arruda (2013)
Captopril and enalapril are two anti-hypertensive medicines that act on the reninangiotensin-aldosterone system by inhibiting ACE. It has been reported for awhile some protective activity over a few courts by these drugs, and they found their ability to regulate the production of some cytokines inhibiting pro-inflammatory and stimulating anti-inflammatory kinds. On the other hand, the incomplete Freund’s adjuvant is known to increase response to immunization and also cause inflammation. The objective was to establish the effects of these medicines on the peripheral blood cells, leucocytes profile, spleen cells, IgG1 specific production and body, spleen and liver weights during the specific immune response. C57BL/6 mice immunized with OVA+IFA were divided into non-treated, enalapril treated and captopril treated groups to monitor de kinetics of peripheral leucocytes, cytokine and IgG1 production and monitoring body weight, spleen and liver. It was found that the drugs did not modulate the amount of circulation leucocytes, did not alter the expected kinetics of each subpopulation percentage on leucocytes induced by adjuvant, spleen cells did not significantly change the weight of body, liver and spleen did not change. It also did not influence the kinetics of the IgG1 production or the amount of antibody produced. Thus, we can conclude that the drugs captopril and enalapril did not alter significantly the immune response parameters analyzed of the immunized animals.